Pengaruh Strategi Membaca Nyaring Scanning dalam Kemampuan Membaca Pemahaman Buku Cerita Pembelajaran Bahasa Indonesia di Kelas III - Nadya Agustina Putri; Agung Setyawan; Sih Widayati (Citra Dharma Cindekia, 2024)
The purpose of this study was to evaluate the effect of reading aloud and scanning strategies on students' reading comprehension skills in Indonesian language learning in grade III. The sample consisted of fifteen students, consisting of ten males and five females, using a quasi-experimental method. The results showed that the implementation of the strategy improved reading comprehension skills. The post-test scores increased compared to the pre-test scores, indicating that the reading aloud and scanning techniques were effective. It is proven that this approach helps students find specific information and understand the text as a whole. To improve students' literacy skills, this study suggests the use of this approach in Indonesian language learning in elementary schools.